Comparative dynamics of self-consciousness of schizophrenic patients and patients with acute and transient psychotic disorders in the process of compulsory treatment - Yur’yeva L.N.; Demura N.A.; Zhur Y.V.; Kolomoyets N.Y.; Kushnir N.G. (Medičnì Perspektivi)
Article presents the materials of empirical research of life sense orientations, self-relation and level of claims of schizophrenic patients and patients with acute and transient psychotic disorders, who have committed socially hazardous actions and to whom forced measures of medical character are temporarily applied. Changes in the self- consciousness of patients with schizophrenia in dynamics were examined: in comparing the results obtained at first and fourth stages of patients' stay in mental hospital with strict supervision (the first stage – adaptation and diagnostics, the fourth stage – the consolidation of treatment results and preparation of patient to be discharged). Research was done by D. Leontiev’s test of life sense orientations (LSO), by S. Pantileyev – V. Stolin’s techniques and by Shwarzlander’s “Motor test”. Statistical processing of the obtained results of differences by indices of life sense orientations, of selfattitude and level of claims between the group under study with Student's t-criterion was used.